Stimulation‐dependent gating of TRPM3 channel in planar lipid bilayers. Issue 3 (9th December 2015) - Uchida, Kunitoshi; Demirkhanyan, Lusine; Asuthkar, Swapna; Cohen, Alejandro; Tominaga, Makoto; Zakharian, Eleonora
Abstract : The transient receptor potential melastatin (TRPM)‐3 channel is critical for various physiologic processes. In somatosensory neurons, TRPM3 has been implicated in temperature perception and inflammatory hyperalgesia, whereas in pancreatic β‐cells the channel has been linked to glucose‐induced insulin release. As a typical representative of the TRP family, TRPM3 is highly polymodal. In cells, it is activated by heat and chemical agonists, including pregnenolone sulfate (PS) and nifedipine (Nif). To define the nuances of TRPM3 channel activity and its modulators, we succeeded in incorporating the TRPM3 protein into planar lipid bilayers. We found that phosphatidylinositol‐4, 5‐bisphosphate (PIP2) or clotrimazole is necessary for channel opening by PS. Unlike PS, the presence of Nif alone sufficed to induce TRPM3 activity and demonstrated distinct gating behavior. We also performed an extensive thermodynamic analysis of TRPM3 activation and found that TRPM3 exhibited slight temperature sensitivity in the bilayers. In the absence of other agonists TRPM3 channels remained closed upon heat‐induced stimulation, but opened in the presence of PIP2, although with only a low open‐probability profile. Together, our results elucidate the details peculiar to TRPM3 channel function in an isolated system. We confirmed its direct gating by PS and PIP2, but found a lack of the strong intrinsic temperature sensitivity common to other thermosensitive TRP channels.—Kunitoshi, U., Demirkhanyan, L., Asuthkar, S., Cohen, A., Tominaga, M., Zakharian, E., Stimulation‐dependent gating of TRPM3 channel in planar lipid bilayers. FASEB J. 30, 1306–1316 (2016). www.fasebj.org